2021
DOI: 10.15244/pjoes/131808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Copper Levels in Feed on Antioxidant Capacity in Stocking the Native Sheep in the Wumeng Prairie

Abstract: The purpose of this research is to better understand the effect of different copper (Cu) levels of feed on the antioxidant capacity in the native sheep, solve the adverse effects of local seasonal Cu deficiency on sheep, and provide a reasonable reference for Cu supplementation. 10 healthy native sheep were selected as the control group (C group). 40 Cu-deficient native sheep were selected as tested group, and divided randomly into 4 groups (n = 10), supplied by CuSO 4 (0, 20, 40, 60 mg/kg for group I, group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Monitoring the oxidant/antioxidant status in the diseased animal revealed a significant increase in serum concentration of MDA with significant decrease in serum enzymatic activities of TAC, GSH-Px, CAT, SOD and Cp. These results were in line with those of [13], who found that a lower intake of Cu in the diet was linked to lower levels of GPx, SOD, and CAT and higher levels of MDA, as well as a decrease in the body's ability to create antioxidants. Conversely, increasing the amount of copper in the diet boosts the body's antioxidant capability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Monitoring the oxidant/antioxidant status in the diseased animal revealed a significant increase in serum concentration of MDA with significant decrease in serum enzymatic activities of TAC, GSH-Px, CAT, SOD and Cp. These results were in line with those of [13], who found that a lower intake of Cu in the diet was linked to lower levels of GPx, SOD, and CAT and higher levels of MDA, as well as a decrease in the body's ability to create antioxidants. Conversely, increasing the amount of copper in the diet boosts the body's antioxidant capability.…”
Section: Discussionsupporting
confidence: 92%
“…SOD is a crucial part of the antioxidant system because it scavenges free radicals in animals, which allows it to oppose and prevent the harm that free radicals do to cells while also repairing the damage over time [45]. Since Cu/Zn-SOD is the most prevalent of the four types of SOD, improving Cu/Zn-SOD production and synthesis can be achieved by raising the level of Cu in vivo [17] [13]. The reaction product of SOD is the substrate of GSH-Px and CAT [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations